Clinico-epidemiological and genomic profile of first Zika Virus outbreak in India at Jaipur city of Rajasthan state. Issue 12 (December 2020) - Malhotra, Bharti; Gupta, Veenu; Sharma, Pratibha; Singh, Ruchi; Sharma, Himanshu; Vyas, Madhavi; Mathur, Ravi P.; Mathur, Virender K.; Meena, Deepa; Malhotra, Hemant; Yadav, Pragya D.; Sapkal, Gajanan; et al.
Abstract: Background: First Zika virus (ZIKV) positive case from North India was detected on routine surveillance of Dengue-Like Illness in an 85-year old female. Objective of the study was to conduct an investigation for epidemiological, clinical and genomic analysis of first ZIKV outbreak in Rajasthan, North India and enhance routine ZIKV surveillance. Method: Outbreak investigation was performed in 3 Km radius of the index case among patient contacts, febrile cases, and pregnant women. Routine surveillance was enhanced to include samples from various districts of Rajasthan. Presence of ZIKV in serum and urine samples was detected by real time PCR test and CDC trioplex kit. Few ZIKV positive samples were sequenced using the next-generation sequencing method for genomic analysis. Result: On outbreak investigation 153/2043 (7.48%) cases were found positive: 1/153 (0.65%) among contacts, 90/153 (58.8%) in fever cases, 62/153(40.5%) in pregnant females. In routine surveillance, 6/4722 (0.12%) serum samples were ZIKV positive.Majority of patients had mild signs and symptoms, no case of microcephaly and Guillain- Barre Syndrome was seen, 25 (40.3%) pregnant females delivered healthy babies, four (6.4%) reported abortion and three (4.8%) had intrauterine death, one (1.6%) child had colorectal malformation and died after few days of birth. ZIKV was found to belong to Asian lineage, mutation related to enhanced neuro-virulence and transmission in animal models was not found. Conclusion: ZIKV was endogenous to India belonging to Asian Lineage. Disease profile of the ZIKV was asymptomatic to mild. No major anomaly was observed in infants born to ZIKV positive mothers; however, long term follow up of these children is required. There is need to scale up surveillance in the virology lab network of India for early detection and control. Summary line: Zika virus infection was endogenous due to Asian Lineage with mild disease, no case of microcephaly or Guillain- Barre Syndrome was seen but children need to be followed for anomalies and surveillance of ZIKV needs to be enhanced in the country.